Multimodal Image Analysis in Acquired Vitelliform Lesions and Adult-Onset Foveomacular Vitelliform Dystrophy - Ricardo Rocha Bastos; Carla Sofia Ferreira; Elisete Brandão; Fernando Falcão-Reis; Ângela M. Carneiro (Journal of Ophthalmology)
Purpose. To characterize vitelliform lesions (VLs) in adult-onset foveomacular vitelliform dystrophy (AOFVD) and acquired vitelliform (AVL) patients using multimodal image analysis. Methods. Retrospective study of twenty-eight eyes from nineteen patients diagnosed with AVL or AOFVD. They were evaluated by color fundus photographs, fundus autofluorescence (FAF), fluorescein angiography (FA), and spectral-domain optical coherence tomography (SD-OCT). Results. Bilateral VLs were associated with AOFVD (p=0.013). Regular and centered VLs were associated with AOFVD (p=0.004 and p=0.016), whereas irregular and noncentered lesions were more frequent in AVL patients. Visual acuity, greatest linear dimension (GLD), lesion height (LH), and pseudohypopyon were similar between groups. Whereas median LH and GLD in AVL group diminished significantly during follow-up (p=0.009 and p=0.001), AOFVD lesions tended to become larger and thicker. Conclusions. When consulting a patient presenting a VL with unknown age of onset, familial history, or previous retinal diseases, some aspects of multimodal imaging assessment may lead the ophthalmologist to a correct diagnosis.